2015
DOI: 10.1097/gox.0000000000000421
|View full text |Cite
|
Sign up to set email alerts
|

A Simple, Easy, and Reliable Technique of Phalangeal Corrective Osteotomy for Overlapping Fingers

Abstract: Background:The theory that malrotation is best assessed by making a fist and looking for digital overlap was the basis for devising a simple, easy, and reliable technique for phalangeal corrective osteotomy.Methods:This study assessed the phalangeal corrective osteotomy technique in 7 digits, involving 7 cases in 6 patients; 1 patient required treatment bilaterally. This technique required the use of a small hologram 2-row plate and screws to maintain stable fixation during aggressive postoperative therapy. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…4 In a similar setting, Abe performed a tenolysis and implant removal in two out of seven patients. 7 As shown in a cadaver model, a dorsally applied plate will displace the extensor mechanism and reduce motion at the proximal interphalangeal joint. 8 The clinical application of IMHS for fixation of corrective osteotomies has not yet been published.…”
Section: Discussionmentioning
confidence: 98%
“…4 In a similar setting, Abe performed a tenolysis and implant removal in two out of seven patients. 7 As shown in a cadaver model, a dorsally applied plate will displace the extensor mechanism and reduce motion at the proximal interphalangeal joint. 8 The clinical application of IMHS for fixation of corrective osteotomies has not yet been published.…”
Section: Discussionmentioning
confidence: 98%
“…Osteotomies at the site of the malunion allow the closest restoration of pre-injury anatomy, but are associated with a high risk of complications and the need for re-operation. Abe (2015) reported that 29% of osteotomies required tenocapsulodesis concomitant with implant removal. Trumble and Gilbert (1998) reported on 11 cases, which all required secondary plate and screw removal.…”
mentioning
confidence: 99%